2023
DOI: 10.1002/htj.22853
|View full text |Cite
|
Sign up to set email alerts
|

Improved heating floor thermal performance by adding PCM microcapsules enhanced by single and hybrid nanoparticles

Abstract: A heating floor is a low‐temperature emitter consisting of pipelines in which a fluid circulates between 35°C and 45°C. To ensure energy efficiency, occupant comfort, and building material durability, proper heat management is crucial in buildings. By using phase change materials (PCMs) in building envelopes, the indoor temperature can be regulated through the storage and release of thermal energy, which reduces energy consumption and enhances occupant comfort. In this study, we evaluated numerically a heating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…ext (1) The external temperature varies between 25°C and 45°C. The indoor air temperature is maintained at 26°C, while the heat transfer coefficients by convection for the interior surface (h int ) and the exterior surface (h ext ) are 5 and 20 W/(m² K), respectively.…”
Section: Climates Zonesmentioning
confidence: 99%
See 1 more Smart Citation
“…ext (1) The external temperature varies between 25°C and 45°C. The indoor air temperature is maintained at 26°C, while the heat transfer coefficients by convection for the interior surface (h int ) and the exterior surface (h ext ) are 5 and 20 W/(m² K), respectively.…”
Section: Climates Zonesmentioning
confidence: 99%
“…Construction accounts for 33% of Moroccan final energy consumption and is rapidly growing. [1][2][3] According to the International Energy Agency, primary energy demand will rise by 37% by 2040. 4 Phase change materials (PCMs) are one of the most promising technologies being investigated in the literature right now to address this issue.…”
Section: Introductionmentioning
confidence: 99%
“…To improve this, conductive nanoparticles are mixed into the PCM to increase the thermal conductivity of the PCM material. Studies have shown that by blending hybrid nanoparticles, such as 1% Cu and 4% Al 2 O 3 , thermal efficiency can be increased and economic benefits can be achieved [11]. Taking into account and carefully selecting suitable materials, their hygroscopic properties and corrosion and hazard levels, as well as thermal and atmospheric stability and costs, the integration of highly conductive additives can improve thermal diffusivity processes and increase the efficiency of thermal latent heat storage [12].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of single and hybrid nanoparticles in different proportions to the PCM layer can enhance the storage capacity of the PCM layer and reduce the internal temperature amplitude by up to 18%. The hybrid nanoparticles allowed for an increase of 4°C and a phase shift of 6 hours 30 minutes compared to a conventional heated floor without PCM 11 …”
Section: Introductionmentioning
confidence: 99%
“…The hybrid nanoparticles allowed for an increase of 4 C and a phase shift of 6 hours 30 minutes compared to a conventional heated floor without PCM. 11 Motahar et al 12 dispersed titanium oxide (TiO 2 ) in Octadecane and experimentally analyzed the temperature effect on thermal conductivity and viscosity. The findings demonstrated that thermal conductivity does not necessarily improve at higher concentrations.…”
Section: Introductionmentioning
confidence: 99%